CISSP (ISC)2 certification practice exams and tests : over 1000 practice questions and explanations covering all 8 CISSP domains for exam version May 2021 - Jordan, Ted (Packt Publishing, 2021)
Pass the Certified Information Systems Security Professional Exam with our all-new set of practice exams designed to simulate the latest exam version Key Features Get ready to take the CISSP exam with the help of practice questions covering all concepts tested in the exam Discover and fill the gaps in your knowledge with detailed explanations of answers Take two full practice exams that simulate CISSP version May 2021 Book DescriptionThe CISSP exam is for security professionals who understand that poor security can put a company out of business. The exam covers eight important security domains - risk management, security architecture, data security, network security, identity management, auditing, security operations, and software development security. Designed to cover all the concepts tested in the CISSP exam, CISSP (ISC)2 Certification Practice Exams and Tests will assess your knowledge of information security and introduce you to the tools you need to master to pass the CISSP exam (version May 2021). With more than 100 questions for every CISSP domain, this book will test your understanding and fill the gaps in your knowledge with the help of descriptive answers and detailed explanations. You'll also find two complete practice exams that simulate the real CISSP exam, along with answers. By the end of this book, you'll be ready to take and pass the (ISC)2 CISSP exam and achieve the Certified Information Systems Security Professional certification putting you in the position to build a career as a security engineer, security manager, or chief information security officer (CISO) What you will learn Understand key principles of security, risk management, and asset security Become well-versed with topics focused on the security architecture and engineering domain Test your knowledge of IAM and communication using practice questions Study the concepts of security assessment, testing, and operations Find out which security controls are applied in software development security Find out how you can advance your career by acquiring this gold-standard certification Who this book is for This book is for existing and aspiring security professionals, security engineers, security managers, and security experts who want to validate their skills and enhance their careers by passing the CISSP 2021 exam. Prior experience working in at least two of the CISSP security domains will be beneficial.